An annotated list of lichenized and lichenicolous fungi of Black sea biosphere reserve (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The data about 104 species of lichenized and 7 species of lichenicolous fungi of Black sea region are given. 30 from them are new for this territory, 17 – excluded from list of lichen biota of reserve. Xanthoria monofoliosa S.Y. Kondr. et Karnef. – is a new species for Ukraine. The species are arranged on the reserve areas Ivano-Rybalchansky, Volyzhyn forest, Tendrivska Kosa, Solenoozerny, Yagorlytsky Kut and Potievka.
Keywords: locations, Tendrivska Kosa, Solenoozerny, Potievka, Ivano-Rybalchansky, Volyzhin forest, Yagorlytsky kut.